Ruptured Corpus Luteum with Hemoperitoneum: Case Characteristics and Demographic Changes Over Time - Wen-Kuang Ho; Ya-Fen Wang; Hsin-Hung Wu; Horng-Der Tsai; Tze-Ho Chen; Ming Chen (Elsevier, 2009)
Objective: Women of reproductive age are at risk of ruptured corpus luteum with hemoperitoneum. We identified the clinical and demographic features of patients recently treated in our institution and compared the findings with those from an earlier series, to detect any changes in disease identity that have occurred over the past 20 years. Materials and Methods: Charts of patients treated between January 2001 and December 2003 at Changhua Christian Hospital were reviewed. Clinical parameters were compared with those from our previous study in the 1980s. Results: A total of 91 women were diagnosed with ruptured corpus luteum and hemoperitoneum (mean age, 26 years; range, 15-42 years). Most ruptures (60.4%) occurred during the secretory phase and most women (57.1%) reported recent sexual intercourse prior to the onset of pain. Most patients (81.3%) required laparoscopic intervention to achieve hemostasis. No obvious differences were found between the results of this study and those from the 1985 series, except that our patients were younger, were more often unmarried, chose laparoscopic interventions rather than laparotomy, and that there was an emerging trend towards conservative treatment. Conclusion: The manifestations of corpus luteum hemorrhage in this study were similar to those observed in the 1980s at the same medical center. However, the demographic parameters (age, marital status) and the modalities of treatment (conservative treatment, mode of surgical interventions) had changed in line with the evolution of society, culture, and the progress of medical science over the past 20 years.